THE IMPORTANCE OF COMPLIANCE WITH ACCOUNTING ETHICS STANDARDS ISSUED BY AAOIFI IN ACTIVATING THE GOVERNANCE OF ISLAMIC BANKS: AN ANALYTICAL STUDY - Ibrahim Kouzo; Falikhatun (Berkala Akuntansi dan Keuangan Indonesia, 2023)
Purpose – This study aims to highlight the importance of complying with the ethical standards issued by (AAOIFI) in activating the governance of Islamic banks and financial institutions. Design/methodology/approach – The descriptive analytical approach was used in the study of ethical standards and governance issued by (AAOIFI) with a review of empirical and descriptive studies related to this subject to derive the importance of compliance with these standards in the governance of Islamic financial institutions, which differ in their philosophy from other conventional institutions. Findings – The study concluded that ethical standards have a significant and essential impact on activating Islamic governance in Islamic financial institutions as one of the foundations of Islamic law from which they derive the reason for their existence and public confidence in them. Originality/value – This study fills in the gaps related to the study of the direct and mutual relationship between ethics and governance in Islamic financial institutions and opens the door to more comprehensive studies on this subject.